Sociodemographic, behavioral, and clinical factors associated with low atrial fibrillation knowledge among older adults with atrial fibrillation: The SAGE-AF study. Issue 1 (January 2021) - Sedney, Colleen; Abu, Hawa O.; Trymbulak, Katherine; Mehawej, Jordy; Wang, Ziyue; Waring, Molly E.; Saczynski, Jane; McManus, David D.
Highlights: Participants aged ≥75 years, without a college degree, with anxiety, and a history of MI, HF, and CI were more likely to have low AF knowledge. Areas of weakness regarding AF knowledge include patient role in AF and basic medication knowledge. Characteristics identified as high risk for low AF knowledge are easily obtainable from patient records and be used for targeted AF education. Abstract: Background: Management of AF requires patient engagement in disease management which requires adequate knowledge about AF. Objective: To identify the patient characteristics associated with low AF knowledge among older adults with AF. Methods: The SAGE-AF cohort enrolled adults aged ≥65 diagnosed with AF in 2016−2018. Patient characteristics associated with low AF knowledge (<6/8 JAKQ items correct) were examined using multivariable adjusted logistic regression models. Results: Participants (N = 950) were on average 74 years old (SD: 6.7), 50 % female, and 87 % non-Hispanic white. The average JAKQ score was 68.7 (SD: 17.1), and 78 % had low AF knowledge. Participants aged ≥ 75 (OR: 1.55, 95 % CI: 1.03, 2.33), without a college degree (OR: 0.46, 95 % CI: 0.32, 0.65), cognitively impaired (OR: 1.72, 95 % CI: 1.15, 2.58), with a history of anxiety (OR: 1.76, 95 % CI: 1.09, 2.83), myocardial infarction (OR: 1.82, 95 % CI: 1.08, 3.07), and heart failure (OR: 1.84, 95 % CI: 1.16, 2.91) were more likely to have low AF knowledge. Practice implications: Characteristics available in the electronic medical record may identify patients at risk for low AF knowledge. Formal assessment of AF knowledge may identify areas of weakness and allow for targeted education.